A synergy‐based control solution for overactuated characters: Application to throwing. (24th November 2016) - Cruz Ruiz, Ana Lucia; Pontonnier, Charles; Levy, Jonathan; Dumont, Georges
Abstract: In the current paper, we present a bio‐inspired solution for the control of overactuated models in animation, such as musculoskeletal models. This solution consists in the extraction of muscle synergies from human experiments, followed by a control method consisting of a series of optimizations to adapt muscle parameters and synergies to match experimental data. We apply the framework on throwing motions, and the results show that these motions can be accurately reproduced on a character with a simplified muscular structure, while preserving important characteristics in the original synergies or control signals. Abstract : We present a low‐dimensional solution for the control of overactuated models in animation, such as musculoskeletal models. Our framework extracts synergies from human subjects and adapts them through a series of optimizations.We apply the framework on throwing motions, and the results show that these motions can be accurately reproduced on a character with a simplified muscular structure, while preserving important characteristics in the original synergies or control signals.